Students (ages 6, 10, and 15 years) in six countries knowledge of animals - Patricia Patrick; Jenny Byrne; Sue Dale Tunnicliffe; Tuula Asunta; Graça S. Carvalho; Sari Havu-Nuutinen; Hrefna Sigurjónsdóttir; Gunnhildur Óskarsdóttir; Rosa Branca Tracana (Nordic Studies in Science Education, 2013)
This article considers the knowledge students (ages 6, 10, and 15 years) have of animals from a cross-cultural perspective. Students from six countries (Brazil, England, Finland, Iceland, Portugal, and the United States of America) were asked to free-list as many animals as possible and state where they had seen or learned about the animals. The results were analyzed and they indicate that 1) Students are aware of animals. 2) Students are more aware of mammals as examples of animals. 3) There is a globally shared folk biological knowledge of animals. 4) Students learn about animals during sociocultural interactions. The educational implications are discussed.